2003
DOI: 10.4049/jimmunol.171.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Uterine NK Cell Population Requires IL-15 but These Cells Are Not Required for Pregnancy nor the Resolution of a Listeria monocytogenes Infection

Abstract: During pregnancy in mice, uterine natural killer (uNK) cells abundantly accumulate on the mesometrial side of the placenta. In this study, we show that the presence of both mature and immature uNK cells requires IL-15. Bone marrow transplantation of NK cell-negative mice due to null mutations in the recombination-activating gene (Rag) 2/common cytokine receptor γ-chain (Rag2−/−γc−/−) genes indicated that uNK cells originate from the bone marrow and require IL-15 to develop. NK cells are thought to be central p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 48 publications
4
132
0
3
Order By: Relevance
“…13 To our knowledge, there is not an ideal marker for murine uNK cells. A cell purification strategy using DBA-lectin and CD122 marker may be more specific for mouse uNK cell purification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 To our knowledge, there is not an ideal marker for murine uNK cells. A cell purification strategy using DBA-lectin and CD122 marker may be more specific for mouse uNK cell purification.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Embryonic day E12.5 was chosen as the gestational time to collect uNK cells because the uNK cells are at peak density on day E10 and have not yet begun to decrease in density through apoptosis (which begins on day E13 or E14). 13 Furthermore, we expected that it would be easier to distinguish healthy embryos from resorbing ones on day E12.5 than at an earlier time point. All animal procedures followed the national animal care guidelines, and associated data were approved for publication by the institutional review board of Shanghai Jiaotong University.…”
Section: Methodsmentioning
confidence: 99%
“…Published data obtained from in situ hybridization studies suggest that macrophages present in the pregnant mouse uterus may be responsible for the production of IL-15 [22], and it has also been shown that macrophages are the major source of IL-12 and IL-18 in most tissues [23,24]. These cytokines were recently shown to be capable of activating NK cells [25,26], and King and co-workers described IL-15 receptor expression on human decidual NK cells [27]. Impaired remodeling of maternal vessels, a hypocellular decidua and decreased development of the metrial gland observed in implantation sites with inhibited recruitment of a4b7 + leukocytes suggest altered uNK cell function, although litter size and birth weight in both b7-integrin -/-and P-selectin -/-mice are comparable to those of untreated or Hermes-1-treated wild-type pregnancies as also reported by Croy et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, injection of recombinant IFN-γ to RAG-2 −/− γ c −/− pregnant females results in decidual vessel modification in the absence of uterine NK cells (Guimond et al, 1998). Interleukin 15 (IL-15) knock-out mice, a third strain deficient in NK cells, present similar decidual anomalies, lacking decidual arteries modifications and decidual integrity (Ashkar et al, 2003;Barber and Pollard, 2003). Thus, in mice, it appears that uterine NK cells are involved in promoting placental development and decidual vessel modifications.…”
Section: Nk Cells During Normal Pregnancy and In Preeclampsiamentioning
confidence: 99%